Quantum dots in imaging, drug delivery and sensor applications - Matea CT; Mocan T; Tabaran F; Pop T; Mosteanu O; Puia C; Iancu C; Mocan L (International Journal of Nanomedicine, 2017)
Cristian T Matea,1,* Teodora Mocan,1,2,* Flaviu Tabaran,1,3,* Teodora Pop,1,4,* Ofelia Mosteanu,1,4,* Cosmin Puia,1,5,* Cornel Iancu,1,5,* Lucian Mocan1,5,* 1Nanomedicine Department, Regional Institute of Gastroenterology and Hepatology “Octavian Fodor”, 2Department of Physiology, University of Medicine and Pharmacy, “Iuliu Hatieganu”, 3Department of Pathology, Faculty of Veterinary Medicine, University of Agricultural Sciences and Veterinary Medicine, 4Department of Gastroenterology, 5Department of Surgery, University of Medicine and Pharmacy, “Iuliu Hatieganu”, Cluj-Napoca, Romania *These authors contributed equally to this work Abstract: Quantum dots (QDs), also known as nanoscale semiconductor crystals, are nanoparticles with unique optical and electronic properties such as bright and intensive fluorescence. Since most conventional organic label dyes do not offer the near-infrared (>650 nm) emission possibility, QDs, with their tunable optical properties, have gained a lot of interest. They possess characteristics such as good chemical and photo-stability, high quantum yield and size-tunable light emission. Different types of QDs can be excited with the same light wavelength, and their narrow emission bands can be detected simultaneously for multiple assays. There is an increasing interest in the development of nano-theranostics platforms for simultaneous sensing, imaging and therapy. QDs have great potential for such applications, with notable results already published in the fields of sensors, drug delivery and biomedical imaging. This review summarizes the latest developments available in literature regarding the use of QDs for medical applications. Keywords: quantum dots, biomedical applications, nanoprobes, theranostic platforms